A low energy consumption WSN node. (2015) - Peng, Jun-jie; Chen, Yuan-yuan
As the basis of internet of things, WSN has been widely studied. According to the difference of applications, many researchers have put forward different architectures and implementations of wireless sensor network. However, most of WSNs are used for complicated scenarios which means they need relatively high energy consumption in the real applications. This means they can not be used in some simple applications, which only need simple data transmission. Based on this situation, we design a low power consumption wireless sensor network node, and present the structure and realisation method. It is simple, reliable, and suitable for the situation in which transmission requirements is not too stringent. Its biggest advantage is super low energy consumption. The experimental results show that the proposed WSN node can reduce 90% of energy consumption compared to that of the widely used ZigBee node on the same conditions.